Integrasi Nilai-Nilai Moderasi Beragama Ke Dalam Rencana Pelaksanaan Pembelajaran (RPP) PAI SMP Kelas IX - Saefudin, Ahmad; Munir, Ahmad Ali; Novitasari, Silvia Putri; Rahmah, Aulia; Ummah, Khoirotul (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2023)
Religious Moderation is very relevant to Indonesia's pluralistic conditions. Religious people are no longer reluctant to acknowledge others, be tolerant, respect various thoughts, reduce fanaticism and violence, and strengthen national insight. The Religious Moderation Module in Islamic Religious Education (PAI) subjects by the Ministry of Religion of the Republic of Indonesia is limited to integrating moderate values ??into Core Competencies (KI), Basic Competencies (KD), and Learning Outcomes (CP). This study aims to identify the values ??of Religious Moderation contained in PAI for class IX SMP and their integration into the Lesson Plan (RPP). In this study, researchers used a qualitative research approach of content analysis or commonly known as qualitative content analysis (QCA). In conclusion, the values ??of Religious Moderation contained in the textbook for PAI and Budi Pekerti Class IX SMP are textual and contextual. These values ??include i'tidal (perpendicular), tasamuh (tolerance), shura (deliberation), tawassuth (moderation), islah (improvement), qudwah (pioneering), muwathanah and (love of the homeland). These values ??are spread out in Basic Competencies in odd semesters and even semesters.